Transplacental infection by bovine alphaherpesvirus type 1 induces protein expression of COX-2, iNOS and inflammatory cytokines in fetal lungs and placentas - Burucúa, Mercedes María; Risalde, María; Cheuquepan Valenzuel, Felipe Andres; Quintana, Silvina; Pérez, Sandra; Canton, German Jose; Moore, Prando Dadin; Odeon, Anselmo Carlos; Agulló-Ros, Irene; Scioli, Maria Valeria; Barbeito, Claudio Gustavo; Morrell, Eleonora Lidia; et al. (Elsevier, 2023)
Bovine alphaherpesvirus type 1 (BoAHV-1) is associated with respiratory and reproductive syndromes. Until present the immunologic mechanisms involved in BoAHV-1 abortion are partially known. We studied key elements of the innate immune response in the placentas and fetal lungs from cattle experimentally-inoculated with BoAHV-1. These tissues were analyzed by histopathology. Furthermore, virus identification was performed by qPCR and the expression of the inflammatory cytokines such as tumor necrosis factor-alpha, interleukin 1-alpha and inflammatory mediators like inducible nitric oxide synthase and cyclooxeganse-2 was evaluated by immunohistochemistry. The viral transplacental infection was confirmed by the detection of BoAHV-1 by qPCR in the placenta and fetal organs, which revealed mild inflammatory lesions. Inducible nitric oxide synthase immunolabelling was high in the lungs of infected fetuses and placentas, as well as for tumor necrosis factor-alpha in the pulmonary parenchyma and cyclooxeganse-2 in fetal annexes. However, the expression of interleukin 1-alpha was weak in these organs. To our knowledge, this is the first study that provides strong evidence of an early immune response to BoAHV-1 infection in the conceptus. Advances in the knowledge of the complex immunological interactions at the feto-maternal unit during BoAHV-1 infection are needed to clarify the pathogenesis of abortion.